EVALUATION OF ISLAMIC EDUCATION CURRICULUM - Fathoni, Wildan; Alim, Khoirul; Yennizar N; Latif , Muhktar (Department of Research and Community Service at the Ummul Quro Al-Islami Bogor Institute, 2025)
This article explores the strategic importance of curriculum evaluation in Islamic education, particularly in the face of global challenges and the digital era. Using a qualitative library research approach, the study discusses four main focuses: the definition of curriculum evaluation, various evaluation models, the implementation of curriculum evaluation in Islamic education, and the core tasks and functions of the curriculum itself. The findings highlight that curriculum evaluation is not only about assessing the effectiveness of learning materials, but also about integrating Islamic values with scientific and technological advancements. Systematic and continuous evaluation is essential to ensure the curriculum remains relevant, adaptive, and capable of producing graduates who are knowledgeable, have strong character, and are ready to face global challenges. The article concludes that effective curriculum evaluation is a strategic instrument for improving the quality of Islamic education in Indonesia, especially in responding to the demands and opportunities of the digital age